2018
DOI: 10.1371/journal.pcbi.1006503
|View full text |Cite|
|
Sign up to set email alerts
|

Demonstrating aspects of multiscale modeling by studying the permeation pathway of the human ZnT2 zinc transporter

Abstract: Multiscale modeling provides a very powerful means of studying complex biological systems. An important component of this strategy involves coarse-grained (CG) simplifications of regions of the system, which allow effective exploration of complex systems. Here we studied aspects of CG modeling of the human zinc transporter ZnT2. Zinc is an essential trace element with 10% of the proteins in the human proteome capable of zinc binding. Thus, zinc deficiency or impairment of zinc homeostasis disrupt key cellular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(27 citation statements)
references
References 70 publications
0
26
0
1
Order By: Relevance
“…ZnT1 contains the canonical HD-DH zinc-binding motif, conserved among zinc transporters 28 . Notably, when comparing the 3D positions of the zincbinding motif (Site A) 29 , in the ZnT1 and ZnT2 models, as well as with the YiiP equivalent Fe/Zn binding site (PDB 3H90), we found similar 3D organization (Fig. 3b).…”
Section: The Structural Implications Of Znt1 Missense Mutations Selecmentioning
confidence: 59%
See 1 more Smart Citation
“…ZnT1 contains the canonical HD-DH zinc-binding motif, conserved among zinc transporters 28 . Notably, when comparing the 3D positions of the zincbinding motif (Site A) 29 , in the ZnT1 and ZnT2 models, as well as with the YiiP equivalent Fe/Zn binding site (PDB 3H90), we found similar 3D organization (Fig. 3b).…”
Section: The Structural Implications Of Znt1 Missense Mutations Selecmentioning
confidence: 59%
“…3b). Given that we have previously shown that the ZnT2 model, which is also based on YiiP, is able to predict the zinc permeation pathway along the transporter 29 , and given the very low homology between ZnT1 and ZnT2 (less than 20% amino acid identity), we believe the similarity in Site A is a good indication of the new ZnT1 model validity, and, in consequence, can be used to rationalize the impact of each of the eight mutants found by this study on ZnT1. Thus, we present here the resulting high-accuracy partial 3D model of ZnT1, focusing on the TM helices, and, using the model, we attempt to rationalize the structural and functional impact of the eight mutations tested in this study, as follows ( Fig.…”
Section: The Structural Implications Of Znt1 Missense Mutations Selecmentioning
confidence: 99%
“…The structural model for the simulation systems of ZnT2 in the inward-facing (IF) and outward-facing (OF) conformations were based on our recent study [21], in which PDB IDs 3H90 (x-ray at 2.9Å resolution [22]) and 5VRF (cryo-EM at 4.1Å resolution [23]) were used as templates for the OF and IF conformations, respectively (see S1 Text for a brief summary of the modeling process). For each system, the transporter homodimer was inserted into a 30 Å-thick particle grid emulating a hydrophobic membrane using the MOLARIS software package [24,25].…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study, we have delineated the putative zinc permeation pathway through the human ZnT2 [21]. Using computational and evolutionary considerations, we determined the residues contributing to the zinc binding site, and modeled the inward- and outward-facing (cytoplasmic- and vesicular lumen-facing, respectively) conformations of ZnT2.…”
Section: Introductionmentioning
confidence: 99%
“…Senyawa asam borat memiliki kelarutan yang sedikit jika dilrutkan di dalam alkohol, (139)(140)(141)(142) cukup larut dalam piridina (143) dan akan sangat sedikit larut (144) ketika pelarutnya aseton. (142; 145-148) Kelarutan suatu senyawa dapat dipengaruhi oleh beberapa faktor diantaranya sifat dari zat terlarut (solute) (149)(150)(151)(152)(153) dan pelarut (154) (solvent) (105; 139; 142; 155; 156) dimana zat terlarut yang bersifat polar (214)(215)(216) akan mudah larut dalam solvent (243)(244)(245)(246) yang bersifat polar begitupun sebaliknya. Suhu, konsentrasi, (106; 149; 157-159) pengaruh penambahan ion senama (236)(237) juga sangat berpengaruh terhadap kelarutan (247)(248)(249) suatu senyawa.…”
Section: Analisis Gapunclassified